A227 UMBILICAL HERNIA INCARCERATION IN LIVER CIRRHOSIS: A RARE COMPLICATION OF PARACENTESIS. (4th March 2021) - LAGROTTERIA, A; Aruljothy, A; Tsoi, K
Abstract: Background: Patients with decompensated liver cirrhosis with ascites frequently have umbilical hernias with a prevalence of 20% and are managed with large volume paracentesis (LVP). Common complications of LVP include hemorrhage, infection, and bowel perforation that occur infrequently with a frequency of less than 1%. However, incarceration of umbilical hernias has been reported as a rare complication of LVP and is speculated to be from ascitic fluid decompression that reduces the umbilical hernia ring diameter resulting in entrapment of the hernia sac. It is unclear whether the quantity or the fluid removal rate increases the herniation risk. Based on case series, this rare complication occurs within 48 hours of the LVP and requires emergent surgical repair and involves a high risk of morbidity and mortality due to potential infection, bleeding, and poor wound healing. Aims: We describe a case report of an incarcerated umbilical hernia following a bedside large-volume paracentesis. Methods: Case report Results: A 59-year-old Caucasian male presented to the emergency department with a 24-hour history of acute abdominal pain following his outpatient LVP. His medical history included Child-Pugh class C alcoholic liver cirrhosis with refractory ascites managed with biweekly outpatient LVP and a reducible umbilical hernia. He reported the onset of his abdominal pain 2-hours after his LVP with an inability to reduce his umbilical hernia. Seven liters of clear, straw-coloured asitic fluid was drained. Laboratory values at presentation revealed a hemoglobin of 139 g/L, leukocyte count of 4.9 x10 9 /L, platelet count of 110 xo 10 9 /L, and a lactate of 2.7 mmol/L His physical exam demonstrated an irreducible 4 cm umbilical hernia and bulging flanks with a positive fluid wave test. Abdominal computed tomography showed a small bowel obstruction due to herniation of a proximal ileal loop into the anterior abdominal wall hernia, with afferent loop dilation measuring up to 3.4 cm. He was evaluated by the General Surgery consultation service and underwent an emergent laparoscopic hernia repair. There was 5 cm of small bowel noted to be ecchymotic but viable, with no devitalized tissue. He tolerated the surgical intervention with no post-operative complications and was discharged home. Conclusions: Ultrasound-guided bedside paracentesis is a common procedure used in the management of refractory ascites and abdominal wall hernia incarceration should be recognized as a potential rare complication. To prevent hernia incarceration, patients with liver cirrhosis should be examined closely for hernias and an attempt should be made for external reduction prior to LVP. A high index of suspicion for this potential life-threatening condition should be had in patients who present with symptoms of bowel obstruction following a LVP. Funding Agencies: None